Tongue-Supported Human-Computer Interaction Systems: A Review - Khan, Masood Mehmood; Sherazi, H.; Quain, R. (IEEE Press, 2014)
The tongue can substitute human sensory systems and has been used as a medium of input to help impaired patients communicate with the world. Innovative techniques have been employed to realize tongue movement, sense its position and exploit tongue dexterity, in order to achieve Tongue Supported Human Computer Interaction (TSHCI). This paper examines various approaches of using tongue dexterousness in TSHCI systems and introduces two infrared signal supported minimally-invasive TSHCI systems developed at Curtin University. Methods of sensing tongue movement andposition are especially discussed and depending on the employed methods, TSHCI systems are categorized as either invasive or minimally-invasive. A set of system usability criteria is proposed to help build more effective TSHCI systems in future.